2021
DOI: 10.1186/s43055-021-00429-w
|View full text |Cite
|
Sign up to set email alerts
|

MRI CSF flowmetry in evaluation of different neurological diseases

Abstract: Background Phase contrast MR imaging is a rapid and non-invasive technique which is sensitive in diagnosis and follow-up of different neurological diseases that cause CSF flow abnormality. MRI CSF flowmetry will be currently assessed in different neurological diseases that may cause CSF flow abnormalities. Results This study includes 39 patients with their ages ranging from 1 to 65 years; they were referred from the neurology department, with nine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Furthermore, phase-contrast MRI examinations conducted on NPH patients revealed significantly greater values in all parameters compared to the control group, consistent with findings by Ahmed et al [15] and Giner et al [16]. The utility of this technique in hydrocephalus classification, particularly in distinguishing communicating from non-communicating hydrocephalus, was underscored.…”
Section: Control (N=18) Nph (N=10) As (N=3) Age-related Brain Atrophy...supporting
confidence: 88%
“…Furthermore, phase-contrast MRI examinations conducted on NPH patients revealed significantly greater values in all parameters compared to the control group, consistent with findings by Ahmed et al [15] and Giner et al [16]. The utility of this technique in hydrocephalus classification, particularly in distinguishing communicating from non-communicating hydrocephalus, was underscored.…”
Section: Control (N=18) Nph (N=10) As (N=3) Age-related Brain Atrophy...supporting
confidence: 88%
“…Alongside its application to neurodegenerative disease, PCC MRI has been utilized to study the impact of CSF flow on many neurologic disorders including iNPH, Chiari malformation, intracranial hyper and hypotension, and obstructive hydrocephalus. In one wide-ranging study, a group of 39 patients stratified along five subgroups (iNPH, hydrocephalus, idiopathic intracranial hypertension, brain atrophy, and Chiari I malformation type) were examined using cardiac-gated sagittal PCC MR image ( Ahmad et al, 2021 ). In the iNPH group, PCC MRI at the level of the cerebral aqueduct found hyperdynamic CSF flow ( Ahmad et al, 2021 ).…”
Section: Phase-contrast Cine Mri (Pcc Mri)mentioning
confidence: 99%
“…In one wide-ranging study, a group of 39 patients stratified along five subgroups (iNPH, hydrocephalus, idiopathic intracranial hypertension, brain atrophy, and Chiari I malformation type) were examined using cardiac-gated sagittal PCC MR image ( Ahmad et al, 2021 ). In the iNPH group, PCC MRI at the level of the cerebral aqueduct found hyperdynamic CSF flow ( Ahmad et al, 2021 ). Additionally, authors were able to use the PCC MRI data to successfully diagnose the exact cause of obstructive hydrocephalus ( Ahmad et al, 2021 ).…”
Section: Phase-contrast Cine Mri (Pcc Mri)mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous animal studies have reported AQP1 expression is closely related to raised ICP through increased CSF production (Stiebel-Kalish et al, 2013), however there is no direct evidence that AQP1 plays the same role in humans. Blood clotting abnormalities Traumatic brain injury N/A # (Xiong et al, 2014) Idiopathic intracranial hypertension N/A Acute patients ", Chronic patients # (Akay et al, 2015;Belal et al, 2020) Normal pressure hydrocephalus N/A " (Ahmad et al, 2021;Bradley, 2015;Tawfik et al, 2017) Ischemic stroke N/A " (Dhar et al, 2020) Post-traumatic syringomyelia N/A # (Yeo et al, 2017) have been reported in IIH patients and may indirectly explain the impaired CSF drainage (Sussman et al, 1997). Moreover, in a recent study female IIH patients present increased hormone levels such as serum testosterone, CSF testosterone and androstenedione (O'Reilly et al, 2019).…”
Section: Idiopathic Intracranial Hypertensionmentioning
confidence: 99%